TRANSFORMATION OF INFORMATION ACTIVITIES IN THE CONTEXT OF DIGITALIZATION OF MODERN SOCIETY - Andrii Sinko (Інтегровані комунікації)
The article examines various aspects of information activities in the context of digital transformation. The author describes the transformation not only as a set of technical changes but also as a deep systemic process that affects the functioning of administrative, social, and communication institutions. The scientific works of researchers have been analyzed, which confirm that digital changes are introducing a new management logic focused on openness, transparency, and efficiency.